Upaya Meningkatkan Aspek Kognitif Melalui Media Papan Angka Bagi Anak Usia 4–5 Tahun Di TK Negeri Malawona - Dhi, Bibiana; Ita, Efrida; Dhiu, Konstantinus Dua; Ngura, Elisabeth Tantiana (Jompa Research and Development, 2025)
This study aims to improve the cognitive aspects of children aged 4-5 years in TK Negeri Malawona through the use of number board media. The method used is Classroom Action Research (CAR) model Kemmis and McTaggart which is implemented in two cycles. The research instruments include observation sheets and documentation. Data analysis is carried out qualitatively and quantitatively. The results of the study showed a significant increase in children's cognitive abilities after the application of the number board media. In the early stages (pre-test), only 31% of children were in the